Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597113
|View full text |Cite
|
Sign up to set email alerts
|

A study of external community contribution to open-source projects on GitHub

Abstract: Open-source software projects are primarily driven by community contribution. However, commit access to such projects' software repositories is often strictly controlled. These projects prefer to solicit external participation in the form of patches or pull requests.In this paper, we analyze a set of 89 top-starred GitHub projects and their forks in order to explore the nature and distribution of such community contribution. We first classify commits (and developers) into three categories: CORE, EXTERNAL and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
0
18
0
Order By: Relevance
“…Rather recent research has showed interest in the investigation of pull request-based Software development [5,8,9,10]. Pull request is a process through which an external or internal collaborator contributes in a project stored in software repositories managed by a DVCS.…”
Section: Pull Request-based Software Developmentmentioning
confidence: 99%
“…Rather recent research has showed interest in the investigation of pull request-based Software development [5,8,9,10]. Pull request is a process through which an external or internal collaborator contributes in a project stored in software repositories managed by a DVCS.…”
Section: Pull Request-based Software Developmentmentioning
confidence: 99%
“…One of the conclusions of Padhye et al [14] is that only 15% of fork projects contain at least one commit. This is strong support for using "forker" and "fork committer" as two roles that are usually ignored in other research.…”
Section: Threats To Validitymentioning
confidence: 97%
“…In GitHub there are two types of projects: root projects (or called first repositories), those that are not forks of other repositories, and fork projects, those that are forks of other repositories [14] [15]. If a developer is interested in a root project, he could fork it and works on the fork project; the code modifications in the fork project can be pushed back to the root project by the pull-request and merge mechanisms; and consequently, his work is merged with the one of other developers of the root project.…”
Section: A Ecosystems Of Floss Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…GitHub Stargazers (e.g. Padhye et al (2014), Ray et al (2014), Casalnuovo et al (2015), Silva et al (2016), and Russell et al (2018)). The rationale behind using popularity as a filtering criterion is that it is assumed to be positively correlated with quality.…”
Section: Related Workmentioning
confidence: 99%